Noncuring Graphene Thermal Interface Materials for Advanced Electronics - Sahar Naghibi; Fariborz Kargar; Dylan Wright; Chun Yu Tammy Huang; Amirmahdi Mohammadzadeh; Zahra Barani; Ruben Salgado; Alexander A. Balandin (Advanced Electronic Materials, 2020)
Abstract Development of next‐generation thermal interface materials (TIMs) with high thermal conductivity is important for thermal management and packaging of electronic devices. The synthesis and thermal conductivity measurements of noncuring thermal paste, i.e., grease, based on mineral oil with a mixture of graphene and few‐layer graphene flakes as the fillers, is reported. The graphene thermal paste exhibits a distinctive thermal percolation threshold with the thermal conductivity revealing a sublinear dependence on the filler loading. This behavior contrasts with the thermal conductivity of curing graphene TIMs, based on epoxy, where superlinear dependence on the filler loading is observed. The performance of the thermal paste is benchmarked against top‐of‐the‐line commercial thermal pastes. The obtained results show that noncuring graphene TIMs outperforms the best commercial pastes in terms of thermal conductivity, at substantially lower filler concentration of φ = 27 vol%. The obtained results shed light on thermal percolation mechanism in noncuring polymeric matrices laden with quasi‐two‐dimensional fillers. Considering recent progress in graphene production via liquid phase exfoliation and oxide reduction, the results open a pathway for large‐scale industrial application of graphene in thermal management of electronics.